Pengabdian kepada masyarakat melalui sosialisasi aspek Riba dan Humanisme dalam transaksi Bank Titil di Desa Jeru - Muzaki, Muhammad Khafid (Maliki Interdisciplinary Journal, 2023)
Financial institutions are an alternative for most people who need funding to meet their life or business needs. However, its existence is still not able to be utilized by some people, especially in rural areas. This occurs for various reasons, such as the lack of information and complicated requirements, so that people in several regions still use the financial services of Bank Titil. From the results of observations of community service conducted for residents of Jeru Village, Turen District, Malang Regency, there are still many who carry out titil bank transactions but do not realize how the law views them and the losses they experience from these loans. This service is carried out as an effort to increase legal understanding and awareness regarding titil bank transactions, community service activities are held through lecture methods and discussions in the form of outreach. As a result, community service has received a positive response from residents because it has the benefit of increasing legal awareness and understanding regarding bank title transactions and being a good medium for residents to gather to harmonize relations between residents.